SFMToolbox: an ArcGIS Python Toolbox for Automatic Production of Maps of Soil Fertility - Velamala, Ranga Rao; Pant, Pawan Kumar (Geomatics and Environmental Engineering, 2023)
SFMToolbox is an ArcGIS Python toolbox developed in ArcGIS Desktop (ArcMap) to perform preprocessing tasks for the automatic creation of maps of soil fertility parameters. Through SFMToolbox, users can automatically produce 12 soil fertility parameter maps as a batch at one time. It is easy to use, where users can only provide input; the output files are automatically created from the name of the sample point and saved in the defined workspace. During the execution of the tools, various processes, such as Inverse Distance Weighted (IDW) – a technique of interpolation, reclassification, adding color, merging, projection, area calculation, and legend are done automatically for all 12 parameters at the same time. The SFMToolbox was validated as part of the following case study: village – Kashipur, tehsil – Balrampur, district – Balrampur, state – Uttar Pradesh, Country – India. The results show that the user can quickly generate maps and save time, improve accuracy, and reduce human intervention and ensure uniformity among maps. This toolbox also applied to Cycle II data from the Government of India’s Soil Health Card (SHC) scheme and timely produced 12-parameters soil nutrient maps for 630 districts in a uniform format. The toolbox may be used by public and private organizations to make timely decisions on agricultural and environmental issues.